2023
DOI: 10.1021/acsomega.2c07755
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzimidazole-1,2,4-triazole Derivatives as Potential Antifungal Agents Targeting 14α-Demethylase

Abstract: Invasive fungal infections (IFIs) are increasing as major infectious diseases around the world, and the limited efficacy of existing medications has resulted in substantial morbidity and death in patients due to the lack of effective antifungal agents and serious drug resistance. In this study, a series of benzimidazole-1,2,4-triazole derivatives (6a−6l) were synthesized and characterized by 1 H NMR, 13 C NMR, and HR-MS spectral analysis. All the target compounds were screened for their in vitro antifungal act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…However, the replacement of the methoxy group and a hydrogen atom on the phenyl moiety with trifluoromethyl and the presence of a longer alkyl chain having carbon atoms from two to seven (compounds 3b – g ) resulted in a loss of action against the two tested strains with MIC values of more than 1024 μg mL –1 , which is similar to the previous report of Khabnadideh et al These findings suggested that the character of the substituents simultaneously determines antifungal activities at the second position and the length of the carbon atoms in the alkyl chain at the first position. In accordance with a previous review, a plausible antifungal mode of action for the synthesized compounds is illustrated in Figure by inhibition of the ergosterol synthesis causing fungal cell membrane degradation. , After crossing the cell membrane, these molecules have previously been reported to be able to inhibit the cytochrome P450 enzyme lanosterol 14α-demethylase (CYP51), , a crucial enzyme that plays an essential role in sterol biosynthesis, especially ergosterol . These molecules reduce the function of 14α-demethylase by interacting with heme iron in the active site and then inducing the enzyme to alter its active site geometry and block the demethylation of lanosterol to ergosterol, one of the fungal membrane’s structural components regulating membrane fluidity and permeability. ,, When ergosterol production is inhibited, the fungal cell wall destabilizes and swiftly disrupts, resulting in the death of the fungus. , …”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…However, the replacement of the methoxy group and a hydrogen atom on the phenyl moiety with trifluoromethyl and the presence of a longer alkyl chain having carbon atoms from two to seven (compounds 3b – g ) resulted in a loss of action against the two tested strains with MIC values of more than 1024 μg mL –1 , which is similar to the previous report of Khabnadideh et al These findings suggested that the character of the substituents simultaneously determines antifungal activities at the second position and the length of the carbon atoms in the alkyl chain at the first position. In accordance with a previous review, a plausible antifungal mode of action for the synthesized compounds is illustrated in Figure by inhibition of the ergosterol synthesis causing fungal cell membrane degradation. , After crossing the cell membrane, these molecules have previously been reported to be able to inhibit the cytochrome P450 enzyme lanosterol 14α-demethylase (CYP51), , a crucial enzyme that plays an essential role in sterol biosynthesis, especially ergosterol . These molecules reduce the function of 14α-demethylase by interacting with heme iron in the active site and then inducing the enzyme to alter its active site geometry and block the demethylation of lanosterol to ergosterol, one of the fungal membrane’s structural components regulating membrane fluidity and permeability. ,, When ergosterol production is inhibited, the fungal cell wall destabilizes and swiftly disrupts, resulting in the death of the fungus. , …”
Section: Resultssupporting
confidence: 70%
“…In accordance with a previous review, a plausible antifungal mode of action for the synthesized compounds is illustrated in Figure 4 by inhibition of the ergosterol synthesis causing fungal cell membrane degradation. 40 , 41 After crossing the cell membrane, these molecules have previously been reported to be able to inhibit the cytochrome P450 enzyme lanosterol 14α-demethylase (CYP51), 19 , 42 44 a crucial enzyme that plays an essential role in sterol biosynthesis, especially ergosterol. 45 These molecules reduce the function of 14α-demethylase by interacting with heme iron in the active site and then inducing the enzyme to alter its active site geometry and block the demethylation of lanosterol to ergosterol, one of the fungal membrane’s structural components regulating membrane fluidity and permeability.…”
Section: Resultsmentioning
confidence: 99%
“…krusei (ATCC 6258), and C. parapsilosis (ATCC 22 019)) according to the microdilution standard methods CLSI M07-A9 (2012) and NCCLS M27-A2 (2002), as described in the previous study. , …”
Section: Methodsmentioning
confidence: 99%
“…The antimicrobial activity of the final compounds ( 5a – i ) was screened against eight species of pathogenic bacteria and three fungal species ( E. coli (ATCC 25922), S. marcescens (ATCC 8100), K. pneumonia (ATCC 13883), P. aeruginosa (ATCC 27853), E. faecalis (ATCC 2942), B. subtilis (NRRL NRS 744), S. aureus (ATCC 29213), S. epidermidis (ATCC 12228), C. albicans (ATCC 24433), C. glabrata (ATCC 90030), C. krusei (ATCC 6258), and C. parapsilosis (ATCC 22 019)) according to the microdilution standard methods CLSI M07-A9 (2012) and NCCLS M27-A2 (2002), as described in the previous study. 25 , 26 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation